Analisis Faktor Kepuasan Pengguna pada Aplikasi Transportasi Online: Pengukuran dengan Metode EUCS dan UTAUT (Studi Kasus: Aplikasi Mobile Maxim) - Anggraini, Nadia; Kurniawan, Dedy; Wedhasmara, Ari; Oktadini, Nabila Rizky; Sevtiyuni, Putri Eka; Rifai, Ahmad (Program Studi Teknik Informatika Universitas Pamulang, 2024)
One of the famous online transportation mobile applications in Indonesia is Maxim. The Maxim mobile application itself has been downloaded by 50 million users and has 1.94 million active application users in the world per week. Based on this data, an application retention rate of 3.88% per week was obtained. It can be said that the application retention rate is still low. One of the reasons for a low retention rate or a decrease in the number of loyal users is poor user experience. Therefore, analysis is needed using a user experience approach, so the user satisfaction model is an appropriate approach. This research aims to analyze user satisfaction factors for online transportation mobile applications with the adoption of the EUCS and UTAUT models. The use of this model includes the variables content, accuracy, format, ease of use, timeliness, and user satisfaction in the EUCS model with the variable performance expectancy, effort expectancy, social influence, facilitating conditions, and behavioral intention contained in the UTAUT model. The data obtained was analyzed using the PLS-SEM technique using the SmartPLS 4 application. The results of this study stated that the variables of content, ease of use, and timeliness had a significant effect on user satisfaction, while accuracy and format had no significant effect. In addition, the variables performance expectancy, effort expectancy, and social influence have a significant effect on behavioral intention, while facilitating conditions show no significant influence on behavioral intention.